PROGRAMMING MULTIPROCESSORS WITH EXPLICITLY MANAGED MEMORY HIERARCHIES. - Schneider, Scott; Jae-Seung Yeom; Nikolopoulos, Dimitrios S. (Computer (00189162), 2009)
The article discusses how to program multiprocessors with explicitly managed memory hierarchies (EMM). The biggest challenge in managing multicore processors with EMM is maintaining its versatility without sacrificing its performance, code complexity and optimization effort. The Cell Broadband Engine processor was used in the experiment to analyze support for expressing parallelism and locality in programming models for multiprocessors with EMM.